Bond behavior of CFRP-to-steel bonded joints at different service temperatures: Experimental study and FE modeling. (2nd January 2023) - Guo, Dong; Liu, Yun-Lin; Gao, Wan-Yang; Dai, Jian-Guo
Highlights: Effects on bond behavior of CFRP-to-steel bonded joints at different service temperatures are investigated. Debonding loads of CFRP-to-steel interface are significantly reduced at low and high service temperatures. A bilinear bond-slip model is developed for the CFRP-to-steel interface at different service temperatures. The results indicate that temperature effects need to be considered appropriately in practical strengthening design. Abstract: The bond behavior of carbon fiber-reinforced polymer (CFRP)-to-steel interface in strengthened steel structures is likely to be significantly affected by service temperature variations, mainly because of interfacial thermal stresses and the changes in the local bond-slip behavior. However, there is lack of comprehensive study on the temperature effects on the bond behavior and the debonding load of the CFRP-to-steel interface at different service temperatures. This paper presents the results from the pull-out tests on CFRP-to-steel double-lap bonded joints tested at service temperatures ranging from −20 °C to 60 °C. The test results including failure modes, debonding loads, load–displacement curves, CFRP strain distributions and interfacial shear stress and slip responses are investigated and compared. Also, a bilinear local bond-slip model is developed to describe the relationships between the shear stresses and the interfacial slips at different service temperatures. A finite element (FE) model is proposed to predict the bond behavior and the debonding loads of the bonded joints at different service temperatures and validated through the comparisons between experimental and FE results. The validated FE model is then used to further investigate the temperature effects on the CFRP strain distributions, interfacial shear stresses and the debonding loads of the bonded joints at different service temperatures. The experimental and FE results have indicated that the debonding loads of the CFRP-to-steel interface are significantly reduced at both low and high service temperatures. The elastic stiffness and the peak shear stress of the local bond-slip model are generally reduced with the service temperature increase, while the interfacial fracture energy decreases at both low and high service temperatures.